The Effect of Barite Addition and Graphite Particle Size on The Specific Abrasion of Fly-Ash/Phenolic Composite for Brake Lining Application - Shirley Savetlana; Zulhanif Zulhanif; Harnowo Supriadi; Irvan Ramadhan; Teten Beliantara (Journal of Engineering and Scientific Research, 2022)
Annually, million tons of fly-ash and bottom fly-ash is a waste of coal power plant. Fly ash contains Iron-oxide, alumina and silica. Those hard particle makes fly-ash can be used as a reinforcement in polymer composite. This composite is a wear resistance material and can be used as material for brake lining application. Fly ash reinforced phenolic composite has a low specific abrasion. The composite for brake lining material consisted of the reinforcement, friction modifier, solid lubricant and filler. Graphite is used as solid lubricant while barite is used as filler. Many research were carried out research on the particle size effect on the composite mechanical properties. However the size different between the constituent in composite has not investigated. Also the optimal barite weight fraction has not being observed. The composite was made by mixing all of the constituent, pressing in the mold and curing. The result show that the graphite particle size ? 150 mm has the lowest specific abrasion. The observation using scanning electron microscope shows that the composite contained small particle of ? 56 mm tends to agglomerate than the composite contained larger particle of ? 150 mm. the composite contained 15% barite has the lowest specific abrasion. The micrograph of scanning electron microscope shows the mixed of phenolic and barite evenly covered the graphite and fly-ash particles.